Post-Mortem Changes in Acetylcholinesterase, Na+/K+ ATPase, Phosphofructokinase, Glutathione Peroxidase, Catalase, and Superoxide Dismutase Activities in Rats Exposed to Toluene - Tuna, Gonca; Dere, Egemen; Mohammed, Abdelazim (The Bulletin of Legal Medicine, 2023)
Objective: Exposure to high doses of toluene, which is widely used in industry, not only causes various symptoms, but can also result in death. The aim of this study is to investigate post-mortem changes in Acetylcholinesterase, Na+/K+-ATPase, Phosphofructokinase and antioxidant enzymes (Glutathione Peroxidase, Catalase, and Superoxide Dismutase) in rats exposed to toluene and to reveal possible post-mortem clues.Methods: Rats were injected with a lethal dose of toluene. Blood, brain and liver tissue were excised at 0, 6, 12, 24 and 48 hours after death.Results: The enzyme activities of toluene groups have been decreased in comparison with the control group for both AChE and PFK enzymes, on the other hand, there was an increase in the Na+/K+-ATPase activity in the brain tissues. In antioxidant enzymes, increases in activity of all 3 enzymes were generally observed when compared to the control group. Plasma GSH-Px activity was observed to decrease between 0-12 hours post-mortem and to increase at 24 and 48 hours post-mortem. GSH-Px activities in the liver showed significant increases at 0, 12 and 48 hours. CAT activities in liver distinctly increased. Significant differences in SOD levels were not detected when compared with the control. Oxidative damage occurring in cells under the effect of toluene may have disrupted the membrane structure, the three-dimensional structure of proteins and lipids, and the cell repair mechanisms.Conclusion: It was determined that oxidative damage due to toluene may cause changes in some enzyme activities in the post mortem period, which may prove oxidative damage.
Keywords: Post-mortem, Biochemistry, Antioxidants, Enzymes, Toluene